Therapeutic strategies for tongue musculature: a systematic literature review - Andressa Colares da Costa Otavio; Arthur Cherem Netto Fernandes; Maria Eduarda Pollachinni Andrade; Brenda Barros Dias; Erissandra Gomes; Marco Aurélio Vaz (CoDAS)
ABSTRACT Purpose To analyze the different therapeutic strategies prescribed in orofunctional rehabilitation of the tongue musculature. Research strategies Regional Portal of the Virtual Health Library for Latin America and the Caribbean, Embase, PubMed/MEDLINE, Scientific Electronic Library Online, SciVerse Scopus and Cochrane databases were consulted, with the descriptors "exercise therapy” OR “physiology” OR “musculoskeletal physiological phenomena” OR “digestive system and oral physiological phenomena” AND “speech therapy” OR “myofunctional therapy” OR “speech language pathology” AND “tongue”. Studies indexed until October 5, 2023, were included. Selection criteria Studies with an interventionist design with exercises for tongue musculature were included. Data analysis Three reviewers selected, extracted and tabulated the information from the studies. The PEDro scale was used to measure the studies’ methodological quality. Results 1.036 studies were found, and 18 were included in this review. The samples varied between 16 and 148 subjects, aged between 4 and 95 years. Only seven studies clearly described the exercises execution, and the number of sets, repetitions, and contraction duration. Fourteen studies clearly defined the exercises’ objectives. The average score of the PEDro Scale analysis was 6.9, and 56.25% of the studies scored ≥7. Conclusion There is a lack of a clear description of the exercises’ goals and their clinical indications, which can lead to confusion and inadequate prescription. Future studies will need to provide a clear description of the outcomes, in order that we can define, according to the exercises and training program specificity, what the effects of different training methodological parameters in this musculature are.